English legal system (Cavendish lawcards, 1997)
The "LawCard" series covers the broad range of subjects available on the undergraduate law programme, as well as on the Diploma in Law course. Each work is a complete, pocket-size guide to key examinable areas of the law syllabus. This work covers the English legal system